The Routledge handbook of the political economy of the environment - Laurent, Éloi; Zwickl, Klara (Routledge international handbooks, 2022)
Featuring a stellar international cast-list of leading and cutting-edge scholars, The Routledge Handbook of the Political Economy of the Environment presents the state of the art of the discipline that considers ecological issues and crises from a political economy perspective. This collective volume sheds new light on the effect of economic and power inequality on environmental dynamics and, conversely, on the economic and social impact of environmental dynamics. The chapters gathered in this handbook make four original contributions to the field of political economy of the environment. First, they revisit essential concepts and methods of environmental economics in the light of their political economy. Second, they introduce readers to recent theoretical and empirical advances in key issues of political economy of the environment with a special focus on the relationship between inequality and environmental degradation, a nexus that has dramatically come into focus with the Covid crisis. Third, the authors of this handbook open the field to its critical global and regional dimensions: global issues, such as environmental justice movement and inequality and climate change as well as regional issues such as agriculture systems, air pollution, natural resources appropriation and urban sustainability. Fourth and finally, the work shows how novel analysis can translate into new forms of public policy that require institutional reform and new policy tools. Ecosystems preservation, international climate negotiations, and climate mitigation policies all have a strong distributional dimension that chapters point to. Pressing environmental policy such as carbon pricing, low-carbon and energy transitions entail numerous social issues that also need to be accounted for with new analytical and technological tools. This handbook will be an invaluable reference, research and teaching tool for anyone interested in political economy approaches to environmental issues and ecological crises. Éloi Laurent is a Senior Economist at OFCE/Sciences Po, France, a Professor at the School of Management and Innovation at Sciences Po and Ponts ParisTech and a Visiting Professor at Stanford University, USA. Klara Zwickl is Assistant Professor at the WU Vienna University of Economics and Business, Austria"--